Technologies and Applications for Decentralized Identity in Healthcare - Barbosa, Daniela; Ebert, Ken; Shatzkin, Keela Rose (Blockchain in Healthcare Today, 2025)
Key discussion points Decentralized identity in healthcare State of the market Key technologies Deployments and real world use cases Hear from those on the front lines implementing this technology successfully for healthcare clients. Learn where the state of business adoption and success stands. Listeners will gain an overall market education in the first of this series featuring Linux Foundation Decentralized Trust and companies demonstrating successful use cases. Questions What’s the role of decentralized identity in healthcare, and how do you define it? What are some of the key use cases you can highlight for the audience? What are the key technologies used? What does the tech stack look like? What’s the role of verifiable credentials? Blockchain? Agents? How do open source, standards, and community development projects drive progress in healthcare and interoperability? What are the business implications and drivers for decentralized ID in healthcare today? Where is it getting traction? Are there success stories to share? What should we expect next in the USA? Audience: providers, regulators, health system leaders, public health leaders, and CTOs